2024
DOI: 10.3389/fimmu.2024.1266230
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and sepsis and sepsis-related death: a Mendelian randomization investigation

Weifeng Shang,
Sheng Zhang,
Hang Qian
et al.

Abstract: BackgroundIt is unclear what the causal relationship is between the gut microbiota and sepsis. Therefore, we employed Mendelian randomization (MR) to determine whether a causal link exists between the two.MethodsThis study used publicly available genome-wide association studies (GWAS) summary data of gut microbiota, sepsis, sepsis (critical care), and sepsis (28-day death in critical care) to perform a two-sample MR analysis. To ensure the robustness of the results, we also conducted a sensitivity analysis.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…Our study identified several taxa, including the orders of Bacteroidales and Victivallales, the Clostridiaceae1 family, and the genera of Clostridiumsensustricto1, Eggerthella, and Holdemanella, demonstrating significant protective effects on OCC. These findings align with previous research (39,40), offering potential applications in the development of new probiotics/ prebiotics for individuals at risk. Moreover, fecal microbiota transplant (FMT) emerges as another promising approach.…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified several taxa, including the orders of Bacteroidales and Victivallales, the Clostridiaceae1 family, and the genera of Clostridiumsensustricto1, Eggerthella, and Holdemanella, demonstrating significant protective effects on OCC. These findings align with previous research (39,40), offering potential applications in the development of new probiotics/ prebiotics for individuals at risk. Moreover, fecal microbiota transplant (FMT) emerges as another promising approach.…”
Section: Discussionsupporting
confidence: 92%